Study on a Moving Mechanism of Movable Disk of Steel Bar Cage Rolling Welder in Construction - Wang Demin; Wang Pengyu; Liu Rongshuai; Wu Honggang (Jixie chuandong)
In order to improve the machining accuracy and stability of the steel cage welding machine and reduce the production cost of the transmission parts,a movable disk walking device is designed. The main core component of the device is a chain transmission mechanism,comprises two chains fixed on the lower track of the movable disk and two groups of sprockets arranged on the side wall of the movable disk base and are mutually mirror symmetrical,wherein each group of sprocket wheels comprises a driving sprocket and two supporting sprockets. In the process of movement,the chain is fixed on the pendulous track,unable to move relatively,drives the disc in a straight line. The prototype test shows that the device has the characteristics of smooth operation,high transmission efficiency,portability and easy installation.